The sounding object - Rocchesso, Davide; Fontana, Federico (Mondo Estremo Publishing, 2003)
During the last couple of decades we have been involved in a revolution: computer-based virtual, distributed, and augmented realities increasingly affect our perception of the world. Despite the abundant technological facilities, we are now faced with lack of knowledge on how to generate sounds which please a perceptual and cognitive system whose evolution developed slowly, over many thousands of years. The authors of this book are striving to find and develop principles that may open the way to get appropriate informative sounds out of future artifacts. They present novel research in perception, physics, numeral analysis, computer science, and human-machine interaction.